2019
DOI: 10.1002/capr.12212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compassion‐focused group therapy on psychological symptoms in mothers of attention‐deficit hyperactivity disorder children: A pilot study

Abstract: Background Evidence suggests that attention‐deficit/hyperactivity disorder (ADHD) may accentuate varying psychological symptoms in parents. Since mothers are the most likely individuals interacting with ADHD children, it is highly probable that they will be influenced the most. Objectives This pilot study aimed to determine the effect of compassion‐focused group therapy on psychological symptoms of mothers of ADHD children. Methods A pre‐test–post‐test control‐grouped, quasi‐experimental study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Self-compassion interventions were delivered as in-person interventions in 28 studies; of these, 24 studies included group-based interventions (Anuwatgasem et al, 2020 ; Arimitsu, 2016 ; Bluth et al, 2016 ; Boggiss et al, 2020 ; Collado‐Navarro et al, 2021 ; D'Alton et al, 2019 ; DeTore et al, 2022 ; Dundas et al, 2017 ; Friis et al, 2016 ; Haukaas et al, 2018 ; Huang et al, 2021 ; Martínez-Borrás et al, 2022 ; Matos et al, 2022 ; Neff & Germer, 2013 ; Noorbala et al, 2013 ; Sajjadi et al, 2022 ; Savari et al, 2021 ; Schuling et al, 2020 ; Shahar et al, 2015 ; Torrijos‐Zarcero et al, 2021 ; Weibel et al, 2017 ; Woodfin et al, 2021 ; Yadavaia et al, 2014 ; Zheng et al, 2022 ) and one study delivered interventions individually (Javidi et al, 2023 ). Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies admini...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-compassion interventions were delivered as in-person interventions in 28 studies; of these, 24 studies included group-based interventions (Anuwatgasem et al, 2020 ; Arimitsu, 2016 ; Bluth et al, 2016 ; Boggiss et al, 2020 ; Collado‐Navarro et al, 2021 ; D'Alton et al, 2019 ; DeTore et al, 2022 ; Dundas et al, 2017 ; Friis et al, 2016 ; Haukaas et al, 2018 ; Huang et al, 2021 ; Martínez-Borrás et al, 2022 ; Matos et al, 2022 ; Neff & Germer, 2013 ; Noorbala et al, 2013 ; Sajjadi et al, 2022 ; Savari et al, 2021 ; Schuling et al, 2020 ; Shahar et al, 2015 ; Torrijos‐Zarcero et al, 2021 ; Weibel et al, 2017 ; Woodfin et al, 2021 ; Yadavaia et al, 2014 ; Zheng et al, 2022 ) and one study delivered interventions individually (Javidi et al, 2023 ). Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies admini...…”
Section: Resultsmentioning
confidence: 99%
“…The average percentage of female participants was 77.8% ( SD = 19.4), ranging from 0 to 100%. A total of 11 studies involved female participants only (Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Kelman et al, 2018 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Navab et al, 2019 ; Noorbala et al, 2013 ; Savari et al, 2021 ; Seekis et al, 2020 ) while one study involved male participants only (Held & Owens, 2015 ). Of the 56 studies, 20 studies directly targeted people who reported psychological distress symptoms, such as depressive symptoms, anxiety, and stress (Anuwatgasem et al, 2020 ; Beshai et al, 2020 ; Bluth et al, 2016 ; Cândea & Szentágotai-Tătar, 2018 ; Collado‐Navarro et al, 2021 ; DeTore et al, 2022 ; Fernandes et al, 2022 ; Guo et al, 2020 ; Javidi et al, 2021 ; Kelly et al, 2009 ; Noorbala et al, 2013 ; Preuss et al, 2021 ; Savari et al, 2021 ; Schuling et al, 2020 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Torrijos‐Zarcero et al, 2021 ; Urken & LeCroy, 2021 ; Yadavaia et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, self-compassion is an important trait to explore in populations, such as those with ADHD, who have poor mental health and more frequent negative experiences than typical, which may require higher levels of resilience. Accordingly, interest in self-compassion and ADHD together has started to gain attention-with researchers investigating self-compassion in parents of children with ADHD (Navab et al 2019), and changes in self-compassion following mindfulness interventions in adults with ADHD (Janssen et al 2019).…”
mentioning
confidence: 99%
“…Additional research shows significant improvements in outcome measures across domains of anxiety (Gharraee et al, 2018;Navab et al, 2019;Noorbala et al, 2013;Sommers-Spijkerman et al, 2018), substance abuse disorder (Carlyle et al, 2019) and eating disorders (Duarte et al, 2017). The available evidence suggests that CFT may be a suitable treatment to address the range of complex symptoms in the emotional stabilisation phase.…”
Section: Compassion-based Interventions As a Treatment For Disturbanc...mentioning
confidence: 99%